2019
DOI: 10.21660/2019.64.08722
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Cement and Asphalt Emulsion Ratios on Cement-Asphalt Emulsion Mortar

Abstract: It is known that cement has been used as a stabilizing agent for the road pavement stabilization. However, it could cause an adverse effect of premature cracking on the road. Moreover, asphalt emulsion has been a famous agent for pavement stabilizing as well, even though it has revealed low deformation resistance. Therefore, this research aims to investigate resulting from the mixture of cement and asphalt emulsion, which is called cement-asphalt emulsion as a new stabilizing agent. This mixture provides more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Cationic asphalt emulsion is used as CAM material because its properties ensure strength in the early stage [9]. It has a lower retardation effect on the hydration process than anionic asphalt emulsion [10]. All these ingredients are mixed and then grouted into the space between the precast concrete slab and the concrete base.…”
Section: Introductionmentioning
confidence: 99%
“…Cationic asphalt emulsion is used as CAM material because its properties ensure strength in the early stage [9]. It has a lower retardation effect on the hydration process than anionic asphalt emulsion [10]. All these ingredients are mixed and then grouted into the space between the precast concrete slab and the concrete base.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al investigated the effects of temperature and powder/binder ratio on the performance of asphalt mortar mixed with limestone mineral powder, cement and coal fly ash. The research showed that reduced temperature or increased filler-asphalt ratio improved the rutting resistance of the mortar with a disadvantageous influence on the low-temperature performance [9][10]. Chen and Li found that replacing all mineral powder with cement improved the workability of the asphalt mixture [11][12].…”
Section: Introductionmentioning
confidence: 99%
“…This retarding effect can increase the initial and the final setting times, allowing AE to significantly retard cement hydration at a high AE to cement ratio [38]. In addition, hydration heat is blocked by thin films of AE on the cement particles, resulting in decreases in mechanical strength and stiffness [39][40][41]. No new crystalline substances or chemical functional groups have been found during the interaction process between cement and the AE [42].…”
Section: Introductionmentioning
confidence: 99%